Perlindungan Hukum terhadap Konsumen atas Sertifikat Tanah Kavling dalam Hal Pengembang telah Dinyatakan Pailit - Sutrisno Sutrisno (JURNAL RECHTENS, 2019)
The population that continues to increase and the limited land area causes a lot of land issuesin the community, the Rungkut area of Surabaya is one example of a region that has manyland problems. When the land buyer paid off the installments, there was a problem on the partof the developer that resulted in the master certificate being destroyed / lost, the poorfinancial condition caused the company to go bankrupt and eventually become bankruptbecause it had a lot of debt in the bank.In resolving land disputes, two routes can be taken,namely out of court (non-litigation) such as conducting consensus / mediation / arbitrationand through court proceedings (litigation) if the settlement with mediation or deliberationreaches no agreement and peace.Keywords: default, mediation, court.